Islamic Militant Movements in Indonesia: A Preliminary Study Accounts for its Socio-Religious and Political Aspects - Bahtiar Effendy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This essay attempts to look at the nature or character of Islamic militancy as reflected in the reemergence of a number of Islamic parties as well as socio-religious organizations of Islamic origins. Circumstance following the downfall of the Soeharto government and the aftermath it has created will be used to put the issue in perspective. Based on the actual strength of both Islamic parties and the newly established socio-religious organizations, this essay also examines the sustainability of such perceived Islamic militancy.DOI: 10.15408/sdi.v11i3.594